Digital Radiographic Evaluation of the Quality of Different Root Canal Obturation Techniques in Deciduous Mandibular Molars after Preparation with Rotary Technique - Mehdi Jafarzadeh; Masood Saatchi; Parisa Jafarnejadi; Morteza Gooran (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Several factors affect the success of pulp therapy of primary teeth, including cleaning and shaping of the root canals and the quality of obturation as the most important steps. Purpose: The aim of the present study was to compare the quality of different root canal obturation techniques in deciduous mandibular molars subsequent to preparation of the root canals with the rotary technique, using the photo stimulated phosphor (PSP) digital radiographic technique. Materials and Method: In this in vitro study, 221 root canals were selected in 80 extracted deciduous mandibular second molars. The root canals were prepared with a modified protocol for ProTaper NiTi rotary files and with only two instruments (SX and S2) and obturated using a lentulo spiral, condensation technique, an anesthetic syringe, and tuberculin syringe techniques with ZOE paste. The quality of the root canal obturation (obturation length and the number and sizes of the voids) was evaluated using PSP radiographic technique. Data were analyzed with SPSS 21, using chi-squared, Kruskal-Wallis and Mann-Whitney tests. Results: There were no significant differences in the obturation length (p= 0.285) and the number of voids (p= 0.061) between the study groups; however, there were significant differences in void sizes between the study groups (p= 0.001). The condensation and tuberculin syringe groups exhibited the best and worst results considering the obturation length, respectively. Lentulo and anesthetic syringe techniques have also exhibited acceptable results. The condensation and anesthetic syringe groups exhibited the minimum and maximum number of voids, respectively. The condensation and lentulo groups exhibited the maximum and minimum void sizes, respectively. Conclusion: If implemented correctly, there will be no significant difference among the experienced root canal obturation techniques considering obturation length and the number of voids.